Utility of Feedback Has a Greater Impact on Learning than Ease of Decoding. Issue 2 (20th November 2019) - Dainton, Chelsea; Winstone, Naomi; Klaver, Peter; Opitz, Bertram
ABSTRACT: While feedback is a key facilitator of learning, researchers have yet to determine the ideal feedback process for optimal performance in learners. The current study investigates the combined effects of ease of decoding, and utility of feedback during learning. Accuracy and rate of learning were recorded alongside changes to the feedback related negativity (FRN), an event‐related potential (ERP) elicited by feedback stimuli. This study investigates the FRN within the context of future‐focused directive feedback (DF), in addition to past‐focused evaluative feedback (EF) typically seen in the neuroscience literature. Results indicate a main effect of utility together with an interaction with ease of decoding on the accuracy data, but only the main effect of utility on learning rate. DF produced an FRN, like EF, which was then larger during high‐utility feedback, specifically following negative EF or when hard‐to‐decode. Implications and future research directions are discussed.